Teaching Chemical Reaction Focus on Nature of Science - Srivastava, Stuti (JOURNAL OF INDIAN EDUCATION, 2018)
Development of students’ understanding of Nature of Science (NOS) is an important aim of scientific literacy. Any science topic can be modified to enhance student understanding about science and how it works. In science classrooms, there should be explicit teaching of the aspects of NOS. In this paper, topic ‘Chemical Reaction’ has been modified to explicitly teach four aspects of NOS — the empirical nature of scientific knowledge, the creative and imaginative nature of scientific knowledge, the tentative nature of scientific knowledge and scientific inquiry.